Ecotourism a case study - Trikojus, Tom; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2002)
This program uses the Philip Island Nature Park (PINP) as a case study to explore and illustrate the principles of ecotourism. The Philip Island Nature Park is an excellent example because it has tours and attractions at all three levels of accreditation, and has been involved in ecotourism for many years
Title from title screen
Executive producer, Mark McAuliffe ; camera, Richard Leigh ; soun, Leigh Tilson, Tom Trikojus ; editor, Michael Henry ; graphic, Reece Sanders
Narration: Julia Martin
Keywords: Ecotourism -- Case studies; Tourism -- Case studies